2006
DOI: 10.1111/j.1467-839x.2006.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological empowerment, job satisfaction and performance among Filipino service workers

Abstract: The present study surveyed 954 employees and their supervisors to determine the relationship of empowerment with job satisfaction and performance in five different service sectors: hotels, food service, banking, call centers, and airlines. Psychological empowerment was positively correlated with both job satisfaction and performance. Although intrinsic motivation was associated with higher levels of empowerment and job satisfaction, contrary to hypothesis, intrinsic motivation did not moderate the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 15 publications
9
82
1
5
Order By: Relevance
“…The study"s findings were supported by previous studies, which confirmed a significant relationship between psychological empowerment and job satisfaction (e.g. Spreitzer, 1996;Hancer and George, 2003;Hechanova et al, 2006;Patah et al, 2009;Pelit et al, 2011). It is worth noting here that psychological empowerment was a more significant predictor of employee job satisfaction than structural empowerment.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The study"s findings were supported by previous studies, which confirmed a significant relationship between psychological empowerment and job satisfaction (e.g. Spreitzer, 1996;Hancer and George, 2003;Hechanova et al, 2006;Patah et al, 2009;Pelit et al, 2011). It is worth noting here that psychological empowerment was a more significant predictor of employee job satisfaction than structural empowerment.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the previous studies have highlighted the significant relationship between empowerment and job satisfaction (e.g. Fulford and Enz, 1995;Spreitzer, 1996;Hancer and George, 2003;Hechanova et al, 2006;Dickson and Lorenz, 2009;Patah et al, 2009;Gazzoli et al, 2010;Pelit et al, 2011). When employees perceived they are empowered and that lead them to have more positive emotional states and their overall attachment to the environment of work (Fulford and Enz, 1995).When empowerment is implemented properly at workplace, it can be effective in improving job satisfaction, performance and productivity (Sashkin, 1984), and therefore empowerment may contribute to enhance job satisfaction (Fulford and Enz, 1995).…”
Section: Empowerment and Job Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…The measure has been validated at the individual as well as team level [20]. It has been shown to be invariant across gender [21], culture [22]- [28] and contexts [30]- [33].…”
Section: Methodsmentioning
confidence: 99%